2015
DOI: 10.1039/c4ra15891a
|View full text |Cite
|
Sign up to set email alerts
|

Stark sublevels in Tm3+–Yb3+ codoped Na2Y2B2O7 nanophosphor for multifunctional applications

Abstract: Phase and crystal structure of the Na 2 Y 2 B 2 O 7 :Tm 3+ -Yb 3+ inorganic phosphor prepared by solution combustion method has been identified by powder X-ray diffraction technique.Surface morphology and particle size has been examined by using the field emission scanning electron microscopy and high resolution transmission electron microscopy characterizations of the prepared materials. No absorption band around 980 nm has been observed in the Tm 3+ doped phosphors, whereas a broad band around 980 nm in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…2(b)). On further increasing the temperature, the UC emission peaks do not appear clear and becomes noisy due to the thermal quenching effect and hence it becomes difficult to measure the FIR due to the low signal to noise ratio [28,29]. The FIR of two thermally coupled energy levels only depends on energy level separation (energy gap) and temperature of the sample [13,18,30,31].…”
Section: Temperature Sensing Studymentioning
confidence: 99%
See 2 more Smart Citations
“…2(b)). On further increasing the temperature, the UC emission peaks do not appear clear and becomes noisy due to the thermal quenching effect and hence it becomes difficult to measure the FIR due to the low signal to noise ratio [28,29]. The FIR of two thermally coupled energy levels only depends on energy level separation (energy gap) and temperature of the sample [13,18,30,31].…”
Section: Temperature Sensing Studymentioning
confidence: 99%
“…Zhang et al reported that the 2 H 11/2 level is also populated from the 4 S 3/2 level by a fast thermalization between these two states [25]. The population transfer from the 4 S 3/2 level to the 2 H 11/2 level is very rapid under the application of external temperature and the transfer of population between two thermally coupled levels is quasi-thermal type [20,28]. Therefore, the well known Boltzmann distribution can be used to describe the thermalization between the two thermally coupled levels by ignoring the effect of self absorption of the fluorescence [33].…”
Section: Temperature Sensing Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the intrinsic thermally coupled energy levels of rare earth ions, the pair energy levels of Stark sublevels can also be thermally coupled and used to investigate FIR versus temperature characteristics [15,16,17,18]. Baxter et al [17], for example, used the coupled energy levels of 2 F 5/2(a) and 2 F 5/2(b) by Stark split of 2 F 5/2 levels in Yb 3+ ions to study FIR properties of Yb 3+ -doped silica fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, upconversion emissions of Tm 3+ ion can be obtained under 980 nm excitation, Yb 3+ ion is usually used as the sensitizer ion to absorb 980 nm photons and transfer the energy to Tm 3+ ion [6,7]. And the thermally coupled energy levels or stark sublevels of Tm 3+ ion are proved to be appropriate for optical thermometry with high sensitivity and good accuracy recently [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%